Clinical Implications of Donor Warm and Cold Ischemia Time in Donor After Circulatory Death Liver Transplantation. Issue 9 (5th June 2019) - Paterno, Flavio; Guarrera, James V.; Wima, Koffi; Diwan, Tayyab; Cuffy, Madison C.; Anwar, Nadeem; Woodle, E. Steve; Shah, Shimul
Abstract : The use of donation after circulatory death (DCD) liver allografts has been constrained by limitations in the duration of donor warm ischemia time (DWIT), donor agonal time (DAT), and cold ischemia time (CIT). The purpose of this study is to assess the impact of longer DWIT, DAT, and CIT on graft survival and other outcomes in DCD liver transplants. The Scientific Registry of Transplant Recipients was queried for adult liver transplants from DCD donors between 2009 and 2015. Donor, recipient, and center variables were included in the analysis. During the study period, 2107 patients underwent liver transplant with DCD allografts. In most patients, DWIT and DAT were <30 minutes. DWIT was <30 minutes in 1804 donors, between 30 and 40 minutes in 248, and >40 minutes in 37. There was no difference in graft survival, duration of posttransplant hospital length of stay, and readmission rate between DCD liver transplants from donors with DWIT <30 minutes and DWIT between 30 and 40 minutes. Similar outcomes were noted for DAT. In the multivariate analysis, DAT and DWIT were not associated with graft loss. The predictors associated with graft loss were donor age, donor sharing, CIT, recipient admission to the intensive care unit, recipient ventilator dependence, Model for End‐Stage Liver Disease score, and low‐volume transplant centers. Any CIT cutoff >4 hours was associated with increased risk for graft loss. Longer CIT was also associated with a longer posttransplant hospital stay, higher rate of primary nonfunction, and hyperbilirubinemia. In conclusion, slightly longer DAT and DWIT (up to 40 minutes) were not associated with graft loss, longer posttransplant hospitalization, or hospital readmissions, whereas longer CIT was associated with worse outcomes after DCD liver transplants.